Considerations concerning the juridical statute of the embryo - Cárdenas Krenz, Ronald (2023)
The article analyses the topic of the statute of the embryo, dividing from a scientific perspective, to derive in his juridical consideration in opposition to different questions that appear concerning the same one; in that sense, it begins with the question about the scientific sustenance of the definition in the Peruvian Constitution of 1993 that recognize the unborn as subject of right since the conception; the text studies different authors and judicial judgments, with the intention of determine at what point the embryo demands protection, considering its human condition.